2018
DOI: 10.1590/1678-992x-2017-0095
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of soil CO2 flux in sugarcane management systems using the Random Forest approach

Abstract: The Random Forest algorithm is a data mining technique used for classifying attributes in order of importance to explain the variation in an attribute-target, as soil CO 2 flux. This study aimed to identify prediction of soil CO 2 flux variables in management systems of sugarcane through the machine-learning algorithm called Random Forest. Two different management areas of sugarcane in the state of São Paulo, Brazil, were selected: burned and green. In each area, we assembled a sampling grid with 81 georeferen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 33 publications
0
4
0
2
Order By: Relevance
“…For the 0.05‐ to 0.10‐m and 0.10‐ to 0.20‐m depths, we observed that the sand feature was selected as the most important to generate the model for prediction of soil C stock. The relationship between clay and C stock is already well established in the literature (Carbonell‐Bojollo, Torres, Rodriguez‐Lizana, & Ordónez‐Fernández, 2012; Razafimbelo et al., 2008; Six, Elliott, & Paustian, 2000; Six et al., 2002), the former being a key feature in the process of stabilization of the C in the soil due to its ability to promote the aggregation of particles and grant physical protection to the organic C stock (Tavares et al., 2018). In contrast, our results pointed to sand as an important feature in the storage of C in the soil.…”
Section: Discussionmentioning
confidence: 91%
“…For the 0.05‐ to 0.10‐m and 0.10‐ to 0.20‐m depths, we observed that the sand feature was selected as the most important to generate the model for prediction of soil C stock. The relationship between clay and C stock is already well established in the literature (Carbonell‐Bojollo, Torres, Rodriguez‐Lizana, & Ordónez‐Fernández, 2012; Razafimbelo et al., 2008; Six, Elliott, & Paustian, 2000; Six et al., 2002), the former being a key feature in the process of stabilization of the C in the soil due to its ability to promote the aggregation of particles and grant physical protection to the organic C stock (Tavares et al., 2018). In contrast, our results pointed to sand as an important feature in the storage of C in the soil.…”
Section: Discussionmentioning
confidence: 91%
“…RF application is beneficial to large-scale data, provides resistance to overfitting, and has recently been used to study the connection between various factors and carbon emissions [ 18 ]. RF has also been used to investigate carbon flux emissions from soils and forests [ 19 , 20 ]. Mascaro et al.…”
Section: Introductionmentioning
confidence: 99%
“…Random Forest (RF) classification is a widely used machine learning algorithm and features advantages of strong resistance to overfitting, good adaption to large-scale data, and variable selection that is not restricted by collinearity. RF algorithms have been previously used to investigate carbon sinks in soils and forests [ 28 , 29 ]. However, little research has investigated the application of RF to influencing factors involved in national and regional carbon emissions (e.g., [ 30 ]).…”
Section: Introductionmentioning
confidence: 99%